Урбанизация в Украине на пороге XXI века - Прибыткова, И. (Социология: теория, методы, маркетинг, 1999)
There have been discussed the characteristic features of urbanization development in Ukraine determining the way of transformation from its extensive stage to intensive one. Special attention has been paid to the new tends, emerged in the last decade, against long-term tends of previous period. The author has analyzed the dynamics and components of city-population growth (1960-1997), the town-net structureas to size and population distribution (1990—1997), periods of city growth (1979—1997). There have been presented some aspects of territorial concentrati on of non-agricultural population in the country, their labor migration, changes of social and professional indicators related to rural population, their growing territorial and social mobile character.